Nanostructure Zinc Oxide Film Based Dye-Sensitized Solar Cell - Teng , Yi Ling; Ahmad, Mohd Khairul (Evolution in Electrical and Electronic Engineering, 2020)
Solar energy is the most abundant renewable source and a continuous source of clean energy. Dye sensitized solar cell (DSSC) is the third generation of solar cells and as a new trend in the photovoltaic technology. DSSC had been widely studied due to it is low cost and high conversion efficiency. Zinc Oxide (ZnO) become potential candidates as the photovoltaic material in DSSC due to its unique properties. Fluorine doped thin oxide (FTO) had been used to fabricate ZnO thin film. Preparation of ZnO thin film were using hydrothermal method in this research. The recipe for prepare the Zinc Oxide (ZnO) solution that used consists of zinc nitrate hexahydrate [(Zn(NO3)2.6H2O], hexamethylenetetramine (HMTA) [C6H12N4] and deionized (DI) water in this research. The ratio of 1:1 for zinc nitrate hexahydrate and hexamethylenetetramine. The growth of ZnO were implemented with various concentration of ZnO solution, which carried out as deposited, 40mM, 60mM, 80mM and 100mM. The dye D149 had been used because of its well absorbance properties for sensitization process. X-ray Diffraction (XRD) is used to determine the crystal substances Moreover, the surface morphology of ZnO nanostructure is characterized by using field emission scanning electron microscope (FE-SEM). Besides, solar simulator acts as an artificial sun to test the behavior of solar cell in this research. Lastly, the sheet resistance and resistivity of ZnO thin film is determined by using two-point probe. The 100mM of ZnO solution concentration is a suitable concentration to grow the nanorods with larger surface area to obtain a higher efficiency.